2016
DOI: 10.3823/2099
|View full text |Cite
|
Sign up to set email alerts
|

Daytime sleepiness in patients with type 2 Diabetes Mellitus – a prospective cohort study

Abstract: Introduction: Daytime sleepiness is an independent factor for increased health care utilization and all cause mortality. Diabetic patients are more likely to be sleepy during the daytime than non-diabetics. Objectives:To examine factors influencing the evolution of daytime sleepiness in patients with type 2 diabetes (T2D) in a two-year followup study.Methods: Patients (N=145) aged from 40 to 60 of both genders were consecutively recruited and evaluated for comorbidity severity (Charlson Comorbidity Index), de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The study by Cass et al (2013) revealed that 64.5% of type 2 diabetes patients with high risk of OSA had excessive daytime sleepiness. A prospective cohort study of type 2 diabetes patients found the prevalence of excessive daytime sleepiness to be 35% (Vasconcelos et al 2016), while in another study conducted on patients with type 1 and type 2 diabetes, the prevalence of excessive daytime sleepiness was 20.7% in the group with OSA (Vale et al 2015).…”
Section: Discussionmentioning
confidence: 95%
“…The study by Cass et al (2013) revealed that 64.5% of type 2 diabetes patients with high risk of OSA had excessive daytime sleepiness. A prospective cohort study of type 2 diabetes patients found the prevalence of excessive daytime sleepiness to be 35% (Vasconcelos et al 2016), while in another study conducted on patients with type 1 and type 2 diabetes, the prevalence of excessive daytime sleepiness was 20.7% in the group with OSA (Vale et al 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Daytime sleepiness was prevalent in this study cohort, which is in accordance with the results of other studies. 34 35 On the other hand, there was a high proportion of participants who dozed when they were sitting, reading, watching TV, or lying down to rest in the afternoon when circumstances permitted. Previous studies have consistently reported that sleep disorders are not only a risk factor for the onset of diabetes but also have a great impact on individuals with T2DM.…”
Section: Discussionmentioning
confidence: 99%